Chimeric siRNAs with chemically modified pentofuranose and hexopyranose nucleotides: altritol-nucleotide (ANA) containing GalNAc–siRNA conjugates: in vitro and in vivo RNAi activity and resistance to 5′-exonuclease. Issue 8 (14th March 2020) - Kumar, Pawan; Degaonkar, Rohan; Guenther, Dale C; Abramov, Mikhail; Schepers, Guy; Capobianco, Marie; Jiang, Yongfeng; Harp, Joel; Kaittanis, Charalambos; Janas, Maja M; Castoreno, Adam; Zlatev, Ivan; et al.
Abstract: In this report, we investigated the hexopyranose chemical modification Altriol Nucleic Acid (ANA) within small interfering RNA (siRNA) duplexes that were otherwise fully modified with the 2′-deoxy-2′-fluoro and 2′- O -methyl pentofuranose chemical modifications. The siRNAs were designed to silence the transthyretin ( Ttr ) gene and were conjugated to a trivalent N -acetylgalactosamine (GalNAc) ligand for targeted delivery to hepatocytes. Sense and antisense strands of the parent duplex were synthesized with single ANA residues at each position on the strand, and the resulting siRNAs were evaluated for their ability to inhibit Ttr mRNA expression in vitro . Although ANA residues were detrimental at the 5′ end of the antisense strand, the siRNAs with ANA at position 6 or 7 in the seed region had activity comparable to the parent. The siRNA with ANA at position 7 in the seed region was active in a mouse model. An Oligonucleotide with ANA at the 5′ end was more stable in the presence of 5′-exonuclease than an oligonucleotide of the same sequence and chemical composition without the ANA modification. Modeling studies provide insight into the origins of regiospecific changes in potency of siRNAs and the increased protection against 5′-exonuclease degradation afforded by the ANA modification.